.06(3t-3)=.18(t-1)+0.00

Simple and best practice solution for .06(3t-3)=.18(t-1)+0.00 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .06(3t-3)=.18(t-1)+0.00 equation:


Simplifying
0.06(3t + -3) = 0.18(t + -1) + 0.00

Reorder the terms:
0.06(-3 + 3t) = 0.18(t + -1) + 0.00
(-3 * 0.06 + 3t * 0.06) = 0.18(t + -1) + 0.00
(-0.18 + 0.18t) = 0.18(t + -1) + 0.00

Reorder the terms:
-0.18 + 0.18t = 0.18(-1 + t) + 0.00
-0.18 + 0.18t = (-1 * 0.18 + t * 0.18) + 0.00
-0.18 + 0.18t = (-0.18 + 0.18t) + 0.00

Reorder the terms:
-0.18 + 0.18t = -0.18 + 0.00 + 0.18t

Combine like terms: -0.18 + 0.00 = -0.18
-0.18 + 0.18t = -0.18 + 0.18t

Add '0.18' to each side of the equation.
-0.18 + 0.18 + 0.18t = -0.18 + 0.18 + 0.18t

Combine like terms: -0.18 + 0.18 = 0.00
0.00 + 0.18t = -0.18 + 0.18 + 0.18t
0.18t = -0.18 + 0.18 + 0.18t

Combine like terms: -0.18 + 0.18 = 0.00
0.18t = 0.00 + 0.18t
0.18t = 0.18t

Add '-0.18t' to each side of the equation.
0.18t + -0.18t = 0.18t + -0.18t

Combine like terms: 0.18t + -0.18t = 0.00
0.00 = 0.18t + -0.18t

Combine like terms: 0.18t + -0.18t = 0.00
0.00 = 0.00

Solving
0.00 = 0.00

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -3x+5y=-22 | | 162n=180n-360 | | 8z+3=9z+8 | | 4(4x-8)=128 | | 0.4/7= | | 3b+8=19 | | 4j^2+6-11j=0 | | 18=x-31 | | m-5/3-5m-5/5=4 | | 170n=180n-360 | | 9=5-t/-5 | | -61=m/12-1 | | 7x-8-3x=x+4+x | | u6=25 | | 44x^3+55x^2-88x-110= | | g(97)+g(97)=97 | | (3p-3p^-1/3p^-1)^-4 | | g(97)-g(97)=97 | | x+19=133 | | -12=-82+12 | | 10x+4y=-14 | | 5v-10=x | | 1234567+87d=-1 | | B-24=16+-3b | | 6x+110+7x+5=180 | | 7(3x-3)-4(3x-15)=2(4x+5)-3 | | 4x-5=5-6 | | x/9=12/15 | | 5.7=-0.6x | | 3(y+5)=6y+13 | | 8v+v+7-8v+2v= | | 45-h(9)=3 |

Equations solver categories